Antimicrobial Activity Test of Medicinal Plant Extract Using Antimicrobial Disc and Filter Paper - Muhammad Taufiq Hidayat; Maharani Pertiwi Koentjoro; Endry Nugroho Prasetyo (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Plant extracts contain secondary metabolites such as flavonoids and phenolic compounds with antibiotic activity. Antibiotic activity test can be done by using the Kirby-Bauer disc method which the antibiotic activity is indicated by the formation of a clear zone. This research was conducted using extracts of Moringa oleifera leaves and Opuntia cochenillifera cladode extracted using ethyl acetate as a solvent. Antibiotic activity test against Staphylococcus aureus bacteria was done in Mannitol Salt Agar and Luria Bertani Agar media. The Kirby-Bauer discs used are Antimicrobial Disc Oxoid® and Filter Paper. The results of this study show that the use of the Antimicrobial Disc Oxoid® and Filter Paper shows no statistical difference in clear zone results (t-value = 0,45; p-value = 0,655; with α = 95%). While the Clear Zone results on Mannitol Salt Agar gave better results than Luria Bertani Agar and were statistically significant (t-value = 2,46; p-value = 0,02; with α = 95%). These findings indicate that filter paper can be an inexpensive alternative for the antibiotic test with no significantly different result compared to commercial antibiotic disc. However, an antibiotic test against Staphylococcus aureus is better done on Mannitol Salt Agar (MSA) compared to Luria Bertani Agar (LBA).